Comparative analysis of the phototoxicity induced by BRAF inhibitors and alleviation through antioxidants. Issue 2 (11th November 2019) - Heppt, Markus V.; Clanner‐Engelshofen, Benjamin M.; Marsela, Enklajd; Wessely, Anja; Kammerbauer, Claudia; Przybilla, Bernhard; French, Lars E.; Berking, Carola; Reinholz, Markus
Abstract: Background: Small molecules tackling mutated BRAF (BRAFi) are an important mainstay of targeted therapy in a variety of cancers including melanoma. Albeit commonly reported as side effect, the phototoxic potential of many BRAFi is poorly characterized. In this study, we evaluated the phototoxicity of 17 distinct agents and investigated whether BRAFi‐induced phototoxicity can be alleviated by antioxidants. Methods: The ultraviolet (UV) light absorbance of 17 BRAFi was determined. Their phototoxic potential was investigated independently with a reactive oxygen species (ROS) and the 3T3 neutral red uptake (NRU) assay in vitro. To test for a possible phototoxicity alleviation by antioxidants, vitamin C, vitamin E phosphate, trolox, and glutathione (GSH) were added to the 3T3 assay of selected inhibitors. Results: The highest cumulative absorbance for both UVA and UVB was detected for vemurafenib. The formation of ROS was more pronounced for all compounds after irradiation with UVA than with UVB. In the 3T3 NRU assay, 8 agents were classified as phototoxic, including vemurafenib, dabrafenib, and encorafenib. There was a significant correlation between the formation of singlet oxygen ( P = .026) and superoxide anion ( P < .001) and the phototoxicity observed in the 3T3 NRU assay. The phototoxicity of vemurafenib was fully rescued in the 3T3 NRU assay after GSH was added at different concentrations. Conclusion: Our study confirms that most of the BRAF inhibitors exhibited a considerable phototoxic potential, predominantly after exposure to UVA. GSH may help treat and prevent the phototoxicity induced by vemurafenib.